Peeping before leaping: push and pull resilience of expatriate adaptation / Abdullahi Ndagi and Anees Janee Ali - Ndagi, Abdullahi; Ali, Anees Janee (Faculty of Hotel and Tourism Management, Universiti Teknologi MARA Selangor, Puncak Alam Campus, 2024)
The world is a marketplace for the good, the bad and the ugly giving rise to activities that either make or mar multinational organisations' endeavours. The global spate of terrorism, racial discrimination, political and religious tensions and conflicts, climate change and degradation, economic instabilities and skirmishes are all attracting the attention of both international management scholars and industry players. In recent, there has been a major focus on expatriate adaptation, particularly in hostile environments. Effective expatriate job performance is established in the literature to be predicated by successful adaptation. Hence, maladaptation leads to expatriate failure and premature repatriation costing those involved huge financial and managerial losses. This article contributes to knowledge and practice by identifying key predictors of expatriate adaptation. Relying on the tenets of Black’s model of adjustment and espousing the anxiety uncertainty management theory, the study examined extant literature leading to the establishment of a research framework that appraises key factors ranging from individual, organisational and environmental that predict expatriate adaptation in a hostile environment.